CURRENT CHALLENGES FOR RESEARCH ACTIVITIES IN THE FIELD OF RAILWAY INFRASTRUCTURE - Otto Plasek (Acta Polytechnica CTU Proceedings)
The increasing importance of railway systems, arising from both national and European strategic documents, leads to increasing demands on its infrastructure. Transport development in the European territory is defined in the strategy summarized in the White Paper, which understands the rail sector as a key sector in terms of sustainability of the transport development due to the suppression of congestions, carbon oxide emissions, reliability and safety of transport. The paper is aimed in the specific technical aspects of rail infrasructure, which emphasize their ability to contribute to an efficient and sustainable transport in Europe and justify motivations for increasing the attractiveness of rail transport. Current challenges for research activities in the field of railway infrastructure that will led to achievement of the objectives which were defined in the White Paper and further specified in the particular requirements of rstakeholders in the railway industry are discussed.